Intra-hour energy potential forecasting in a central solar power plant receiver combining Meteosat images and atmospheric extinction. (1st December 2019) - Alonso-Montesinos, J.; Monterreal, R.; Fernández-Reche, J.; Ballestrín, J.; Carra, E.; Polo, J.; Barbero, J.; Batlles, F.J.; López, G.; Enrique, R.; Martínez-Durbán, M.; Marzo, A.
Abstract: In the search for techniques that control the final energy reaching the receivers of central solar power plants, this work presents a novel combination of several methodologies for establishing a complex and valuable system within the user operating system. To establish the final energy level in the central receiver, the direct normal irradiance (DNI) was predicted at ground level using METEOSAT images combined with a novel system involving two digital cameras that determine atmospheric E x t i n c t i o n in the lower atmospheric layer. The predicted values were used as inputs for a solar plant model (Fiat-Lux) to trace the path of the sunlight according to the mirror features. The flux simulations presented a normalized root-mean square error (nRMSE) below 6% and correlation coefficients (R) above 0.94 when compared to real and predicted values. Therefore, it would be possible to quantify the losses produced in the path between the heliostats and the central receiver by integrating different technologies. Highlights: The total power and irradiance peak have been predicted in the CESA-I CSTP plant. DNI forecasting was predicted by using MSG images at Plataforma Solar de Almería. The extinction was included in the DNI prediction by using two digital cameras. The size and form of the flux distribution were simulated by using Fiat-lux model. The nRMSE was lower than 6% comparing experimental and predicted total power.